A Lifetime International Migration: An Analysis of Migration Factors Among Indonesian Migrant Workers from Sumbawa in Malaysia - Hasyim, Taufiqurrahman; Muktiyanto, Ali; Usman, Indrianawati; ., Wahyu (Journal of Ecohumanism, 2024)
International migration among Indonesian Migrant Workers (IMW) from Sumbawa, West Nusa Tenggara, is closely related to the lack of job opportunities, low labor wages, and low educational qualifications, resulting in the need to leave their hometowns to migrate to another countries that provide a decent life. This paper aims to analyze a phenomenon, namely the factors of IMW from Sumbawa Island practicing lifelong international migration in Malaysia. Using a quantitative method, the sample used was 189 key informants who were recorded using a purposive sampling technique. The data collection tool uses questionnaires as quantitative data and interviews as compilation data for reinforcement. Prerequisite test analysis shows that the data is normally distributed, then data analysis uses a multinomial logistic regression model. The first result obtained was the factor of marriage to a local citizen or foreigner who had Permanent Resident (PR) status. Second, the factor of having obtained full or temporary Malaysian citizenship status. The factors with the highest chance of influencing are the marriage factor in the destination country and PR status with the percentage of the influencing factor of the marriage factor in the destination country being 0.0602 times, the influencing factor of Permanent Resident Status is 0.0321 times, the chance of the factor education is 0.0263 times, and opportunities for security are 0.0126 times. The multinomial logistic regression model obtained is influenced by variable X1, namely: Marriage in the destination country, X2 is Permanent Resident Status, X3 is Education, and X4 is Security factor.